Chemical Composition of Essential Oils of Bulbs and Aerial Parts of Two Cultivars of Allium sativum and Their Antibiofilm Activity against Food and Nosocomial Pathogens - Filomena Nazzaro; Flavio Polito; Giuseppe Amato; Lucia Caputo; Rosaria Francolino; Antonio D'Acierno; Florinda Fratianni; Vincenzo Candido; Raffaele Coppola; Vincenzo De Feo (MDPI AG, 2022)
This work aimed to evaluate the chemical composition of the essential oils (EOs) of two cultivars of Allium sativum and their antibiofilm activity against the food pathogens Acinetobacter baumannii, Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus. The crystal violet assay ascertained the susceptibility of the bacterial biofilms, while the MTT assay let to evaluations of the metabolic changes occurring in the bacterial cells within biofilms. Their chemical composition indicated some sulfuric compounds (i.e., allicin, diallyl disulfide, and allyl propyl disulfide), and decene as some of the main components of the EOs. The aerial parts and bulbs' EOs from the two cultivars showed chemical differences, which seemed to affect the antibiofilm activity. The EOs from aerial parts of 'Bianco del Veneto' inhibited the biofilm formation of L. monocytogenes and E. coli (60.55% and 40.33%, respectively). In comparison, the 'Staravec' EO inhibited the cellular metabolism of E. coli (62.44%) and S. aureus (51.52%) sessile cells. These results indicate their possible use as preserving agents in the food industry and suggest their potential exploitation in the development of new formulations to avoid or limit nosocomial infections.